The synergy tool: Making important quality gains within one healthcare organization - Enoch Ho; Elaine Principi; Charissa P. Cordon; Yayra Amenudzie; Krista Kotwa; Sarah Holt; Maura MacPhee (Administrative Sciences, 2017)
Background: Evidence-based clinical care delivery begins with comprehensive assessments of patients' priority needs. A Canadian health sciences corporation conducted a quality improvement initiative to enhance clinical care delivery, beginning with one acute care site. A real-time staffing tool, the synergy tool, was used by direct care providers and leadership to design and implement patient-centered care delivery. The synergy tool is the patient characteristics component of the Synergy Model™, developed by an expert panel of nurses in the 1990s. Since then, the tool has been effectively used to assess a variety of patient populations on eight important characteristics, informing real-time staffing decisions. Methods: Plan-Do-Study Act cycles were managed by department-based project teams with assistance from business analytics and a quality/safety officer. Results: Initial findings demonstrate reductions in nurse missed breaks, improved workload management, and significant increases in staff engagement. Conclusions: The synergy tool is an easy-to-use tool that can be used to highlight priority care needs for individual patients or specific patient populations. The tool informs real-time staffing decisions, ensuring a better fit between patient needs and nurse staffing assignments. Although this initiative began with nurses, project work is expanding to include inter-professional teams.
Keywords: 350; synergy tool; patient-centred care; PDSA cycles; quality improvement collaboratives